2013
DOI: 10.1177/1741134313483749
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the post-patent entry of generic medicines in Malaysia: A survey of the Malaysian generic pharmaceutical industry

Abstract: Malaysia is reliant on the availability of generic medicines to contain the rising national pharmaceutical expenditure. This paper assesses the factors determining the market entry of a new generic medicine following patent expiration on the innovator product in Malaysia. Data were gathered by using mail survey approach. The prevalidated Likert-scale questionnaire was mailed to all licensed members of the Malaysian Organization of Pharmaceutical Industries. A usable response rate of 53.8% (14/26) was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…As reported for other countries, the findings of this present study thus suggest the existence of certain barriers to immediate entry of generic medicines following patent expiration in Malaysia. A recent study conducted in Malaysia showed that patenting strategies by innovators are the foremost entry‐barriers to generic medicines in Malaysia . Generic entry delays obviously have implications on pharmaceutical expenditures.…”
Section: Discussionmentioning
confidence: 99%
“…As reported for other countries, the findings of this present study thus suggest the existence of certain barriers to immediate entry of generic medicines following patent expiration in Malaysia. A recent study conducted in Malaysia showed that patenting strategies by innovators are the foremost entry‐barriers to generic medicines in Malaysia . Generic entry delays obviously have implications on pharmaceutical expenditures.…”
Section: Discussionmentioning
confidence: 99%
“…[13,16,19,21,22] Five studies suffered from low response rates. [11][12][13]15,[17][18][19] Four studies used convenience sampling, [16,20,22] and two studies were of a small sample size, [14,16] which might have had an impact on generalization.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…(2013) [11] National survey Mail survey 14 Generic manufacturers A small portion of the respondents indicated that the regulatory provision (i.e. Bolar provision) is either effective (21.4%) or highly effective (14.3%) in promoting early post-patent entry of generic medicines.…”
Section: Findings Limitationmentioning
confidence: 99%
See 2 more Smart Citations